Purwarupa Sistem Kontrol Elevator Berbasis Programable Logic Control - Fathahillah Fathahillah; Hardianto Hardianto (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2017)
Various methods / types of controls developed in accordance with industry needs one of them in the field of building automation system. One of the controls in the field of building automation system is the elevator control system (elevator). Early elevator control systems that transport humans or goods as vertical transportation vehicles are still conventional using human power, then evolved using steam engines, until now the elevators use AC motors equipped with control systems. The purpose of this research is to design the prototype of elevator control system using programmable logic control (PLC). The type of PLC controller used in the study using Omron PLC. The results show the design of prototype of elevator control system using PLC successfully and can control eleveator in accordance with its function, besides its programming form can be more simple.